Photosynthetic Acclimation of Symbiodinium in hospite Depends on Vertical Position in the Tissue of the Scleractinian Coral Montastrea curta - Lichtenberg, Mads; Larkum, Anthony W. D.; Kühl, Michael (Frontiers in Microbiology, 2016)
Coral photophysiology has been studied intensively from the colony scale down to the scale of single fluorescent pigment granules as light is one of the key determinants for coral health. We studied the photophysiology of the oral and aboral symbiont band of scleractinian coral Montastrea curta to investigate if different acclimation to light exist in hospite on a polyp scale. By combined use of electrochemical and fiber-optic microsensors for O2, scalar irradiance and variable chlorophyll fluorescence, we could characterize the physical and chemical microenvironment experienced by the symbionts and, for the first time, estimate effective quantum yields of PSII photochemistry and rates of electron transport at the position of the zooxanthellae corrected for the in-tissue gradient of scalar irradiance. The oral- and aboral Symbiodinium layers received ∼71% and ∼33% of surface scalar irradiance, respectively, and the two symbiont layers experience considerable differences in light exposure. Rates of gross photosynthesis did not differ markedly between the oral- and aboral layer and curves of PSII electron transport rates corrected for scalar irradiance in hospite, showed that the light use efficiency under sub-saturating light conditions were similar between the two layers. However, the aboral Symbiodinium band did not experience photosynthetic saturation, even at the highest investigated irradiance where the oral layer was clearly saturated. We thus found a different light acclimation response for the oral and aboral symbiont bands in hospite, and discuss whether such response could be shaped by spectral shifts caused by tissue gradients of scalar irradiance. Based on our experimental finding, combined with previous knowledge, we present a conceptual model on the photophysiology of Symbiodinium residing inside living coral tissue under natural gradients of light and chemical parameters.